#### Answer

$y'= -2+3x^{-4} $
$y'' = -12x^{-5}$

#### Work Step by Step

$y= 4 - 2x - x^{-3}$
$y'= 0-2+3x^{-4} $
$y'= -2+3x^{-4} $
$y'' = 0-12x^{-5}$
$y'' = -12x^{-5}$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y'= -2+3x^{-4} $
$y'' = -12x^{-5}$

$y= 4 - 2x - x^{-3}$
$y'= 0-2+3x^{-4} $
$y'= -2+3x^{-4} $
$y'' = 0-12x^{-5}$
$y'' = -12x^{-5}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.